Sosialisasi Edukasi Keuangan dan Berwirausaha Sejak Dini di SDN 096135 Rambung Merah Kecamatan Siantar Kabupaten Simalungun - Darwin Damanik; Pawer Darasa Panjaitan; Elidawaty Purba; Dian G Purba; Pandapotan Damanik; Yosi Irawelda Saragih; Dina Revani Saragih (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Early financial education outreach activities are designed to educate young people about the correct use of money, wise financial management, the importance of saving for the future and entrepreneurship from an early age. Activities carried out at SDN 096135 Rambung Merah Siantar. The educational method used includes delivering material through direct teaching. Focus group discussions to provide input and evaluation of services. The results of the activity show that children have a low level of education and entrepreneurship, understand money only as a tool to buy the things they want, and do not actively save. They also reported that their parents encouraged them to save and gave pocket money only for snacks or buying toys but still did not teach their children enough to be entrepreneurs. Even though there were challenges, all participants were very enthusiastic about participating in the activity, asking lots of questions and following directions from the service team.